Analisis Framing Pemberitaan Kasus Ferdy Sambo di CNN Indonesia.Com Serta Pemanfaatannya Sebagai E-Modul Teks Berita Kelas VII - Putri, Larasati Windu; Syafroni, Roni Nugraha; Maspuroh, Uah (Jurnal Ilmiah Wahana Pendidikan, 2024)
Information is a primary need for the community, especially in Indonesia. This is because news contains reports of an event or events, situations, and conditions that are important and interesting to meet the curiosity of the audience. The news we read is the result of social construction involving the views, ideologies, and values of a media. The existence of the media demands accuracy, accuracy, and facts that have truth. The objectives of this study are 1) To describe the results of the framing analysis of the news of the Ferdy Sambo case in the January 2023 edition of CNN Indonesia.com online media through the Zhongdang Pan and Gerald M. Kosicki model framing analysis approach 2) To determine the use of the results of the Zhongdang Pan and Gerald M. Kos model framing analysis for Indonesian learning.